2p*2-6=-11

Simple and best practice solution for 2p*2-6=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2p*2-6=-11 equation:


Simplifying
2p * 2 + -6 = -11

Reorder the terms for easier multiplication:
2 * 2p + -6 = -11

Multiply 2 * 2
4p + -6 = -11

Reorder the terms:
-6 + 4p = -11

Solving
-6 + 4p = -11

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 4p = -11 + 6

Combine like terms: -6 + 6 = 0
0 + 4p = -11 + 6
4p = -11 + 6

Combine like terms: -11 + 6 = -5
4p = -5

Divide each side by '4'.
p = -1.25

Simplifying
p = -1.25

See similar equations:

| 97-5*x-2x=48 | | 25+100x=625 | | x-0.29x=438.07 | | 5/2•38.2 | | 10x^2+9=16x^2+9 | | m/sqrt3-11=4 | | 5x+5+4x+2=52 | | (s-6)+(8s+4)= | | -120/(-20)= | | 10+0.10a=0.35a | | 97-5*x=48+2*x | | 12(p-2.33)=8 | | x^2+15+40=4 | | 10+0.10a=0.35 | | 22-s/7=-5 | | 8×5.5/11 | | -60-7n=4+9n | | 1.5x+20= | | 0.5x^2=8x-0.625 | | 3(x-4)-5x=-2x+10 | | y=3(10-2) | | X-0.20x=485.20 | | y=3(8-2) | | 12/(-2)= | | .29x=125-x | | y=3(2-2) | | n-2.2=3.1 | | 52-(2x+6)=2(x+8)+x | | -7-3v=2v+45 | | X+.20x=485.20 | | 2n=10.6 | | 8K=76I |

Equations solver categories